Design of a Low Cost Remotly Operated Vehicle with 3 Dof Navigation - Romi Wiryadinata; Annisa Sucianti Nurliany; Imamul Muttakin; Teguh Firmansyah (Bulletin of Electrical Engineering and Informatics, 2017)
One type of underwater robot is the ROV (Remotely Operated Vehicle) whose movements are controlled directly by humans from the water surface. In this paper, ROV prototype has been designed and tested with three DoF (Degrees of Freedom) and controlled by a joystick which is connected with UTP (Unshielded Twisted Pair) cables as data transmission between joystick with a microcontroller embedded in the robot. This prototype has 3 thrusters with 3 degrees of freedom, 1 rotational motion (heave) and 2 translational motion (yaw and surge), with direction of movement up, down, forward, backward, turn right, and turn left. Speed mode setting when forward movement on PWM (Pulse Width Modulation) 75% = 0,037 m/s, 90% = 0.053 m/s and 100% = 0,071 m/s, while the reverse speed by 75% = 0,034 m/s, 90% = 0.045 m/s and 100% = 0.059 m/s, when the ROV moves up is 0,042 m/s, down 0.032 m/s, turn right 9 o/s and turn left 15 o/s set with fixed PWM value, is 100%.